Auswirkungen des demografischen Wandels auf die Innovationsfähigkeit von KMU: Handlungsfelder für das Personalmanagement - Birgit Verworn (Brandenburg University of Technology Cottbus, Chair of Organization, Human Resource & General Management, 2007)
– As a consequence of the demographic change, the workforce is aging and shrinking at the same time. Based on the resource-based view of the firm, we discuss implications for innovation and human resource management in SMEs. A review of the literature and empirical studies show that a shortage of engineers is becoming on obstacle to innovation in German SMEs and therefore a challenge for human resource management. We present three strategies to counter the possible shortage of skilled engineers.
Keywords: 330; workforce; aging; shrinking; innovation management; HRM; resource-based view